Designing and Implementing Educational Philanthropic Scale - Джахангір Алам (Філософія освіти)
Philanthropy plays a significant role in developing and promoting education over the world. The motives of philanthropy have been studied by designing different scales, most of which are based on the behavior of non-philanthropists, some scales even contain reverse answers for which complexity arises in calculating the scores, there have been limited studies on the educational philanthropic scale too. Danobir Dr. Syed Ragib Ali is one of the renowned philanthropists in Bangladesh, there are a good number of studies on his philanthropic contribution but very few of them focused on the level of educational philanthropy of Dr. Ali. This study aims to critically revisit the existing philanthropic scales so far to design an educational philanthropic scale and assess the level of educational philanthropy of Danobir Dr. Syed Ragib Ali using the newly formed scale. After carefully reviewing the literature, the study initially designed a 35-item ‘Educational Philanthropic Scale (EPS)’ and conducted a purposive online survey among 400 different levels of educational entrepreneurs in Bangladesh. Then, an exploratory factor analysis was conducted from the usable 317 responses and finally, a 27-item scale was prepared. The Cronbach’s Alpha has been tested for reliability and the Kaiser-Meyer-Olkin (KMO) calculated for sampling adequacy. By using this scale it is found that Danobir Dr. Syed Ragib Ali is an exceptionally educational philanthropist. The findings of this study significantly contribute to the existing literature and can broadly be used to assess the educational philanthropic levels within individuals and organizations. The future researcher can find a new horizon to update the scale.